Perfil proteômico da urina para detecção de potenciais biomarcadores para a doença renal crônica - Silva, Nathália Rabello (2024)
Introduction: The growing number of people with chronic kidney disease (CKD), caused mainly by changes in lifestyle and the aging of the population, demonstrates the need to identify new biomarkers that enable the monitoring of the progression of CKD and, consequently, the prediction for end-stage renal disease (ESRD). Objective: To analyze the proteomic profile in urine samples from healthy individuals and those in the final stage of the disease to identify potential biomarkers for CKD. Methodology: Urine samples were collected from 10 healthy individuals and 10 with end-stage CKD. These samples were analyzed according to the following steps of the shotgun methodology: protein precipitation, colorimetric detection and protein measurement, in-solution digestion and peptide desalting. Next, the peptides were analyzed using liquid chromatography equipment coupled to a tandem mass spectrometer and, finally, bioinformatics, gene ontology and protein interaction research was carried out. Results: 416 proteins were identified in the proteomic profile of the analyzed groups and 19 proteins showed statistically significant differences between the groups. Of these, five proteins (hemopexin, beta-2-microglobulin, retinol-binding protein 4, transthyretin and factor D) were considered potential biomarkers for CKD. Conclusion: The proteins found were able to characterize and differentiate the urinary proteomic profiles of the two groups. Also, the five selected proteins can be seen as potential candidates for CKD biomarkers.